Meta-heuristic techniques for optimal design of analog and digital filter - El Beqal Asmae; Kritele Loubna; Benhala Bachir; Zorkani Izeddine (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper, two Meta-heuristic techniques; namely ant colony optimization (ACO) and genetic algorithm (GA) have been applied for the optimal design of digital and analog filters. Those techniques have been used to solve multimodal optimization problem in infinite impulse response (IIR) filter design and to select the optimal component values from industrial series as well as to minimize the total design error of a 2nd order Sallen-Key active band-pass filter, also a comparison between the performances reached by those two Meta-heuristics was made in this article.